Rare additional chromosomal abnormalities in acute promyelocytic leukaemia resulting in rapidly fatal disease: report of a case - Ahmed Maseh Haidary; Sarah Noor; Sahar Noor; Maryam Ahmad; Ahmad Walid Yousufzai; Ramin Saadaat; Zeeshan Ansar Ahmed; Abdul Jamil Rasooli; Ahmad Shekib Zahier; Haider Ali Malakzai; Abdul Sami Ibrahimkhil; Samuel Sharif; et al. (eJHaem, 2022)
Abstract Background Acute promyelocytic leukaemia results from reciprocal translocation between the long arms of chromosomes 15 and 17. This translocation leads to the formation of chimeric gene, which is both the diagnostic marker as well as the therapeutic target of the disease. Additional chromosomal abnormalities are randomly encountered either at diagnosis or during therapy. Here, we present a case of acute promyelocytic leukaemia that had a rare cytogenetic profile at diagnosis. Case presentation Our patient was a 14‐year‐old boy, who presented with characteristic clinical and morphological features of acute promyelocytic leukaemia. Karyotypic analysis revealed trisomy of chromosome 8 with deletion of 9p in addition to t(15;17). The patient passed away within the first 8 h of presentation while receiving conventional chemotherapy and haemodynamic resuscitation. Conclusion Our patient presented with a rare cytogenetic profile and rapidly progressive disease. According to our extensive literature search, this was the first case of acute promyelocytic leukaemia having pathognomonic t(15;17) along with trisomy 8 and 9q deletion.